KARAKTERISASI KATEKIN DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK BUNGA KANGKUNG PAGAR (Ipomea carnea) - Ermi Abriyani; Iin Lidia Putama Mursal; Lia Fikayuniar; Hasnimar hasnimar (Jurnal Buana Farma, 2023)
According to several studies, Kangkung Pagar (Ipomoea carnea Jacq.) that have many beneficial properties. Theaim of this study are to characterize the secondary methabolites from ethanol extract and determine antibacterialactivity against Pseudomonas aeruginosa. Methode s of this study are maceration by ethanol, fractionation bycolumn chromatography and antibacterial activity assay by disc diffusion method. Melting point of compound139-140ºC. The results from characterization by Uv-Vis and IR spectroscopy is flavan 3-ol or catechin. Theresult of antibacterial activity against psudomonas aeruginosa had strong level of activity.